Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Canada. Assez de vies volées ! Discriminations et violences contre les femmes autochtones au Canada : une réaction d'ensemble est nécessaire - Amensty International (Amnesty International, 2009)
La gravité des violences qui s’exercent contre les femmes autochtones du Canada est très élevée. Le présent rapport montre que la réaction des différents niveaux de gouvernement aux menaces qui pèsent sur les femmes des communautés autochtones est inadaptée et parcellaire. Le gouvernement canadien a le devoir indiscutable et impératif de garantir la sécurité des femmes autochtones, de en justice les auteurs de violences à leur encontre et de s’attaquer aux problèmes de fond que sont la marginalisation et la pauvreté.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminicide; féminisme autochtone; histoire et politique; intersectionnalité; journalisme; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's Native and northern series, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques

Itinéraires d'égalités. Trajectoires des femmes autochtones du Québec et du Canada - Levesque, Carole; Labrecque, Marie France (30e anniversaire de l’Association des Femmes Autochtones du Québec, 2007)
À l’occasion du 30e anniversaire de l’Association des Femmes autochtones du Québec, ces actes de colloque proposent de revoir le parcours des femmes autochtones dans leurs luttes pour l’égalité et la justice sociale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; environnement; féminisme autochtone; histoire et politique; inégalités; justice sociale; mexique; militance; pol4105; premier cycle; pédagogie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes